2005
DOI: 10.1103/physrevc.71.044601
|View full text |Cite
|
Sign up to set email alerts
|

Isospin dependence ofHe6+poptical potential and the symmetry energy

Abstract: A consistent folding analysis of the elastic p( 6 He, 6 He)p scattering and charge exchange p( 6 He, 6 Li * )n reaction data measured at E lab = 41.6A MeV has been performed within the coupled channels formalism. We have used the isovector coupling to link the isospin dependence of 6 He+p optical potential to the cross section of p( 6 He, 6 Li * )n reaction exciting the 0 + isobaric analog state (IAS) at 3.563 MeV in 6 Li. Based on these results and the Hartree-Fock calculation of asymmetric nuclear matter usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 45 publications
5
60
0
Order By: Relevance
“…115 CDM3Y6 interaction [159]. Khoa also deduced a symmetry energy of about 30 MeV at ρ ≈ ρ 0 from the coupled-channel analysis of the (p,n) charge-exchange reaction [517,518]. This result is consistent with earlier conclusions of several other studies using different approaches.…”
Section: 05supporting
confidence: 81%
“…115 CDM3Y6 interaction [159]. Khoa also deduced a symmetry energy of about 30 MeV at ρ ≈ ρ 0 from the coupled-channel analysis of the (p,n) charge-exchange reaction [517,518]. This result is consistent with earlier conclusions of several other studies using different approaches.…”
Section: 05supporting
confidence: 81%
“…The dotted curve correspond to the parameterization adopted by Heiselberg et al [14] in their studies on neutron stars, and obtained by fitting the 5 predictions of the variational calculations of Akmal et al [15]. Finally, the solid square point in the figure correspond to the value of symmetry energy obtained by fitting the experimental differential cross-section data in a charge exchange reaction using the isospin dependent optical potential by Khoa et al [16]. The parameterized forms of the density dependence of the symmetry energy obtained from all these studies are as shown in table I.…”
Section: Resultsmentioning
confidence: 99%
“…The blue solid point in the figure correspond to the symmetry energy obtained by constraining the experimental energy of giant dipole resonance (GDR) in 208 Pb by Trippa et al [35]. The square solid point in the figure correspond to the symmetry energy obtained by fitting the experimental differential cross-section data in a charge exchange reaction using the isospin dependent interaction of the optical potential by Khoa et al [36,37]. The green solid curve in the figure is the one obtained from the dynamical AMD model comparison of the experimental isoscaling data assuming the sequential decay effect to be small [3,6].…”
Section: Current Status Of the Density Dependence Of The Symmetry Enementioning
confidence: 99%
“…Trippa et al [35], have studied the symmetry energy from the correlation between the symmetry energy and the experimental centroid energy of the Giant Dipole Resonance (GDR) in 208 Pb nuclei. Khoa et al [36,37], have studied the symmetry energy from the folding model analysis of the charge exchange p( 6 He, 6 Li)n reaction measured at 41.6 MeV/A. Danielewicz [38] have studied the symmetry energy by constraining the binding energy, neutron skin and the isospin analogue state of finite nuclei.…”
Section: Symmetry Energy From Other Studiesmentioning
confidence: 99%